Improving Public Toilet Environment and Hygiene Practices in an Asian City: Voices From Hong Kong Residents. (May 2021) - Sun, Kai Sing; Lam, Tai Pong; Tang, Wai Sin; Chan, Hoi Yan; Lam, Kwok Fai; Chow, Enoch Ching Yeung; Wu, Dan; Zhou, Xu Dong; Xu, Jia Yao; Ho, Pak Leung
Toilet hygiene is an important preventive measure for infectious diseases, including severe acute respiratory syndrome (SARS) and COVID-19. This study explored public's opinions on improving toilet environment and hygiene practices in Hong Kong. A mixed-method approach was applied. We conducted 4 focus groups plus 3 individual interviews among the Hong Kong Chinese, followed by a questionnaire survey with 300 respondents recruited from various districts. Difference in response distributions between groups with different demographics was tested by Pearson χ 2 test. Instead of advocating for advanced toilet facilities, respondents were mostly concerned about basic hygiene issues. Malfunctioning facilities resulting from poor toilet management, such as clogged toilets, stained facilities, and problematic flushing systems, were most cited as barriers to toilet hygiene practices. Three quarters of the survey respondents expressed concerns over worn and poorly maintained toilets, shortage of janitors, and cleansing supplies. However, respondents who were older ( P < .001), less educated ( P < .001), and had lower income ( P = .001) were significantly more likely to find hygiene conditions in public toilets satisfactory. The findings reflected the substandard of the current provisions as a developed city in Asia. Enhanced efforts by the government to maintain basic toilet supplies and facilities is the key to improving public compliance to toilet hygiene practices.